Performance Analysis of Closed Queueing Networks - Lagershausen, Svenja; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This book deals with the performance analysis of closed queueing networks with general processing times and finite buffer spaces. It offers a detailed introduction to the problem and a comprehensive literature review. Two approaches to the performance of closed queueing networks are presented. One is an approximate decomposition approach, while the second is the first exact approach for finite-capacity networks with general processing times. In this Markov chain approach, queueing networks are analyzed by modeling the entire system as one Markov chain. As this approach is exact, it is well-suited both as a reference quantity for approximate procedures and as extension to other queueing networks. Moreover, for the first time, the exact distribution of the time between processing starts is provided.
1. Introduction -- 2. Closed Queueing Networks -- 3. Literature Review -- 4. Decomposition Approach -- 5. Markov-chain Approach -- 6. Distribution of the Time between Processing Starts -- 7. Conclusion.
Keywords: Economics; Mathematical statistics; Operations research; Economics/Management Science; Production/Logistics/Supply Chain Management; Operation Research/Decision Theory; Statistics and Computing/Statistics Programs